Public Places, Intimate Spaces. The Modern Flâneuse in Rhys, Barnes, and Loos - Johanna M. WAGNER (E-REA)
While the clever, detached, and entitled flâneur freely made his way about town, women historically were limited in their urban mobility, which made them invisible as critics of urban modernity. The flâneuse was an unimaginable notion.By hypothesizing an embodied flâneuse, this study will examine modern novels whose characters engage in flânerie in ways that may be at once similar and distinctive regarding the tradition. Three authors who present compelling figures of the flâneuse are the British author Jean Rhys, and American authors Djuna Barnes, and Anita Loos. The protagonists in these select texts obviously do not embody the “traditional” flâneur figure; however, their participation expands the timbre of flânerie by examining the urban and social populous from an alternative point of view.